Pengaruh Model Pembelajaran GQGA (Giving Question and Getting Answer) terhadap Hasil Belajar Siswa - Sri Nengsih; Risky Oktaria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of the application of the GQGA (Giving Question and Getting Answer) learning model to the learning outcomes of Biology students in class X MIPA SMAN 1 Payakumbuh District. This research is a quantitative study, using quasi-experimental methods (quasi experiment) with Randomized posstest only control design. The study population was students. Obtaining samples with random sampling techniques. Based on these techniques, obtained class X MIPA 1 as an experimental class of 22 samples and class X MIPA 2 as a control class of 25 samples. Data analysis technique was performed using t-test with α = 0.05. The results of data analysis obtained t-count = 2.52 ˃ t-table = 1.67 at 95% confidence level, which means the hypothesis is accepted, which means that there is an influence of GQGA learning models on student Biology learning outcomes. The conclusion of the application of the GQGA learning model has a significant influence on student Biology learning outcomes. Keywords: ecology, giving question and getting answer (GQGA), learning model